Isolasi atau Integrasi Sosial: Peran Kualitas Pertemanan dalam Menunjang Kepuasan Hidup Dewasa Muda Lajang di Indonesia - Giofanny Jessica Kaparang; Karel Karsten Himawan (Universitas Gadjah Mada, 2021)
Marriage is a normative practice in Indonesia. As a result, many view marriage as a social achievement rather than a personal choice. This attitude could impact the psychological well-being of single individuals as they receive marriage pressures and associated stigma from their communities. This quantitative study aims to explore the role of friendship quality on life satisfaction among non-dating unmarried young adults in Indonesia. Friendship Quality Scale (FQS) and Satisfaction With Life Scale (SWLS) were employed to measure the quality of friendship and the life satisfaction of 121 unmarried young adults who is not in a romantic relationship in Indonesia (Mage = 29.98; SD = 3.849), as approached through purposive sampling. Result of this study confirmed a significant contribution (49.4%) of friendship quality to the life satisfaction of male participants, but the results among the females was found insignificant.